Growth of GaN layers using Ga2O vapor obtained from Ga and H2O vapor. (7th April 2015) - Sumi, Tomoaki; Taniyama, Yuuki; Takatsu, Hiroaki; Juta, Masami; Kitamoto, Akira; Imade, Mamoru; Yoshimura, Masashi; Isemura, Masashi; Mori, Yusuke
Abstract: In this study, we performed growth of GaN layers using Ga2 O vapor synthesized from Ga and H2 O vapor. In this process, we employed H2 O vapor instead of HCl gas in hydride vapor phase epitaxy (HVPE) to synthesize Ga source gas. In the synthesis reaction of Ga2 O, a Ga2 O3 whisker formed and covered Ga, which impeded the synthesis reaction of Ga2 O. The formation of the Ga2 O3 whisker was suppressed in H2 ambient at high temperatures. Then, we adopted this process to supply a group III precursor and obtained an epitaxial layer. X-ray diffraction (XRD) measurement revealed that the epitaxial layer was single-crystalline GaN. Growth rate increased linearly with Ga2 O partial pressure and reached 104 µm/h.